Antimicrobial Resistance of 914 Beta-Hemolytic Streptococci Isolated from Pharyngeal Swabs in Spain: Results of a 1-Year (1996–1997) Multicenter Surveillance Study - Baquero, Fernando (American Society for Microbiology, 1999)
A nationwide susceptibility surveillance study of beta-hemolytic streptococcal isolates from pharyngeal swabs obtained in 11 Spanish hospitals between May 1996 and April 1997 against 12 antibiotics was carried out. Of the isolates 86% (786 of 914 isolates) were group A and 8.4% (77 of 914 isolates) were group C. No resistance was found to β-lactam antibiotics, but significant differences (P < 0.001) with respect to lack of susceptibility to macrolides were found between groups (27% for group A and 12% for group C) and between seasons (13.2% in summer and 31.7% in winter). Most of these isolates displayed the M phenotype (low-level resistance to erythromycin and susceptibility to clindamycin).